Konsep Esse dan Ens dalam konstruksi politik menjelang Pemilu 2024: Sebuah analisis media sosial : Tinjauan filsafat Thomas Aquinas mengenai "Being” - Siga, Ayub Bertolomeus (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2024)
The focus of this research is to examine more deeply the meaning of Esse and Ens in the political construction ahead of the 2024 elections in Indonesia. The author places social media analysis as an important part of the political construction of the 2024 elections by way of a philosophical review of Thomas Aquinas and Martin Heidegger. The purpose of this research is to express the idea of Esse and Ens in social media regarding the hot issue of the 2024 election. The main objective is to criticize the philosophical meaning of Esse and Ens behind the news circulating in the community. Social media plays a vital role in studying and observing the political development of the 2024 elections in Indonesia. The concept of Esse and Ens provides a sharp injection that election construction is also related to the philosophical meaning of metaphysical studies. Social media can ultimately be seen as something that exists (Ens) and an understanding of 2024 election politics (Esse). The research method used is a critical reading of several sources in the form of articles from various journals on Esse and Ens, literature books on the role of social media in the complexity of modern life. The finding of this paper is that the role of social media in the form of Ens affects the lives of Indonesian people. So that with a significant influence it makes the understanding of the politics of the 2024 elections stronger and more correct. Because the review of Thomas Aquinas and Martin Heidegger becomes real and rooted in the social life of Indonesian society.